Who Participates in Seasonal Influenza Vaccination? Past Behavior Moderates the Prediction of Adherence. (23rd August 2011) - Ernsting, Anna; Lippke, Sonia; Schwarzer, Ralf; Schneider, Michael
Abstract : Background. Vaccination effectively prevents seasonal influenza. To promote vaccination adherence, it is necessary to understand the motivational process that underlies vaccination behavior. This was examined along with the moderating influence of past behavior on intention formation. Methods. German employees (N = 594) completed questionnaires at baseline and at 7-month followup. Regression analyses were conducted for mediation and moderated mediation. Results. Intention at Time 1 mediated the effect of risk perception, and positive and negative outcome expectancies on Time 2 vaccination. Past behavior moderated this effect: there was a mediation effect for risk perception and outcome expectancies only for those individuals who did not participate annually. Conclusions. Risk perception and outcome expectancies influenced intentions to receive vaccination, which in turn predicted participation. Hence, these social-cognitive variables could be targeted in vaccination campaigns to increase intentions. However, vaccination experience affected the formation of intentions and should be accounted for when developing interventions.